2014
DOI: 10.1245/s10434-014-3499-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Causes of Death in Patients Cured of Esophageal Cancer

Abstract: Careful follow-up including the surveillance of other primary cancers is required for long-term survivors of esophageal cancer after esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…24 In addition, we identified pulmonary diseases as the most common cause of death in patients cured of esophageal cancer after esophagectomy. 25 The present study found that RF is deteriorated even at the late phase after esophagectomy and supports the findings of our previous studies. Unfortunately, we could not identify the risk factors for the deterioration of RF at the late phase after esophagectomy.…”
Section: Discussionsupporting
confidence: 93%
“…24 In addition, we identified pulmonary diseases as the most common cause of death in patients cured of esophageal cancer after esophagectomy. 25 The present study found that RF is deteriorated even at the late phase after esophagectomy and supports the findings of our previous studies. Unfortunately, we could not identify the risk factors for the deterioration of RF at the late phase after esophagectomy.…”
Section: Discussionsupporting
confidence: 93%
“…4 The strongest prognostic factor is tumour stage, the 5-year survival is 65% for stage I, 27% for stage II and 9% for stage III. 4 Other prognostic factors are older age, 86,87 higher hospital volume and surgeon volume. 6, 88 Figure 6.…”
Section: Mortalitymentioning
confidence: 99%
“…In this sense, it is difficult to know whether these patients can be considered “cured” of their disease. 8,9 Here we report data on survival and recurrence in patients with LAEC surviving at least 5 years after resection, as well as other causes of death in this highly selected patient population. Because we assumed that patients with early-stage disease are highly likely to be cured of EC, 10 we focused on patients with locally advanced disease treated with either esophagectomy alone or preoperative therapy followed by resection.…”
Section: Discussionmentioning
confidence: 95%